PENGEMBANGAN MEDIA KOMIK INTERAKTIF UNTUK MENGEKSPLOR KEMAMPUAN PROSEDURAL MATEMATIS PESERTA DIDIK KELAS V SEKOLAH DASAR - Fany Lindra Lestari; Supratman Supratman; Sri Tirto Madawistama (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
The purpose of this study was to develop learning media, as well as to test the feasibility and see the responses of students to determine the effectiveness of the mathematical procedural abilities of grade V students of SDN 4 Sukajadi through interactive comic learning media assisted by the storyboard.that web application on the material of cube volume. This research method uses Research Development (RnD) using the Luther Sutopo model. The research data were obtained from interviews, questionnaires, and essay test questions on mathematical procedural abilities. The data sources for this study were obtained from grade V mathematics teachers of SDN 4 Sukajadi, two media experts and two material experts to assess the technical quality, content quality and objectives, and grade V students of SDN 4 Sukajadi to assess the effectiveness of mathematical procedural abilities. The results of this study produced interactive comic learning media through the storyboard.that web application that can be used via smartphones with the title Volume of Cubes. This learning media can be declared feasible by media experts with a percentage of 73.5% and declared very feasible by material experts with a percentage of 82%. This media also has an effectiveness of 1.684 with a high effect size classification for measuring the procedural abilities of class V students at SDN 4 Sukajadi with a good response in its use.